CURCUMIN AND L CYSTEINE SUPPLEMENTATION IN SEMEN EXTENDER MITIGATE CRYOPRESERVATION-INDUCED CRYODAMAGE IN BARBARI BUCK SEMEN SEMEN - Kumar, Dr. Rajesh; Jayanth MN; Singh, Bhoopendra; Srivastava, Sushant; Singh, Jaswant; Verma, 6. Manoj Kumar (The Indian Journal of Animal Sciences, 2026)
Artificial insemination with frozen semen has made a significant contribution to the widespread propagation of sperm, limiting the spread of sexually transmitted diseases. The study aimed to evaluate effect of curcumin (1.0 μg/mL and 2.0 μg/mL ) and L cysteine (2 mM/L and 5 mM/L) supplementation in semen extender mitigate cryopreservation-induced cryodamage in barbari buck semen semen. The present experiment was carried out on four Barbari bucks, reared at Deep Frozen Semen Lab, College of Veterinary Sciences & Animal Husbandry, ANDUAT, Kumarganj, Ayodhya, Uttar Pradesh. Twenty-four ejaculates (six from each buck) were collected, processed, frozen, and evaluated for various seminal markers. In conlusion, the post thaw seminal attributes were significantly higher except sperm abnormality in all treatments groups than those of control. Furthermore, enzyme leakage were significantly lower in treatment group than those of control one. In conclusion, the supplementation of 2µg/ml Curcumin seems to be beneficial in mitigating cryopreservation-induced cryodamage.